[FIHSIHKAHLVRRCHUWAHL<>]: prototyping architectural user-interfaces in urban public space. (2017) - Cameron, Robert; Smolik, Andrei
[FIHSIHKAHLVRRCHUWAHL<>] (heretofore FV), was a design research project into the development of an 'architectural user-interface' (AUI), a built structure that operates as a mediator between human beings and computational information. Through its use of computer vision and gestural interactions, the FV project aimed to develop a novel approach to the design of AUIs whose interactions occurred in relation to the space of the architecture rather than being limited to separate interfaces such as mobile phones or control terminals. In this paper, the concept, structure, and software of the project is outlined in detail. The advantages and disadvantages of this approach are then discussed in relation to the installation and testing of an initial prototype within a public space in Perth, Western Australia. This paper aims to provide research outcomes which may contribute to future interdisciplinary research in the fields of architecture, urban design, interactive public art, and HCI design.